A new species of Amolops monticola group (Amphibia: Ranidae) from Hoang Lien Range, northwest Vietnam - Nguyen, Luan Thanh; Tapley, Benjamin; La, Toi Van; Rowley, Jodi J. L. (Zootaxa, 2025)
Of the 19 species of Amolops reported from Vietnam, 10 are known to occur in the Hoang Lien Range in northwest Vietnam. During field surveys in the Hoang Lien Range, we collected individuals from a population of Amolops that we could not assign to any known species; morphological and molecular data assign these individuals to the Amolops monticola group and we describe a new species to science, Amolops spicalinea sp. nov, in reference to a line of horny spinules running along the body below the dorsolateral fold in males. The new species is morphologically and molecularly most similar to Amolops bellulus from Yunnan Province, China but is distinguished from A. bellulus and other congeneric species by a combination of the following characters: (1) SVL of adult males 46.6–52.2 mm, N=3; adult females 60.1–63.0 mm, N=3; (2) vomerine teeth in two oblique rows between choanae; (3) tympanic annulus visible; (4) all finger and toe tips expanded to discs with circummarginal grooves present; (5) skin smooth, except for lateral surfaces of head, below the dorsolateral fold, and the area surrounding cloaca where the texture varies from tiny spinules to large tubercles; (6) dorsolateral fold present with horny spinules along the lower half in males; (7) creamy-white lip stripe extending from tip of snout, terminating in a broken, rugose line above axilla; (8) dorsum reddish brown or greenish brown with numerous small black spots; flanks yellowish brown to dark brown; ventral surface of body orange-yellow with small brown spots present on chest and throat; (9) interdigital finger webbing absent; toes fully webbed to discs except on Toes IV where webbing reaches discs as a fringe, webbing formula: I0–0II0–0III0–1+IV1+–0V; (10) outer metatarsal tubercles absent; (11) vocal sac absent in males, and (12) nuptial pad velvety without spines. Our phylogenetic analysis using 16S ribosomal RNA mitochondrial gene and cytochrome c oxidase subunit 1 (CO1) genes show that Amolops spicalinea sp. nov. is sister to Amolops bellulus 2 from Yunnan, China. The new species is currently known from only three localities in the Hoang Lien Range between 2288–2493 m asl and is threatened by habitat loss and degradation. This species likely qualifies for being assessed as Endangered in accordance with the IUCN Red List of Threatened Species categories and criteria (B1ab).